A reasoned approach towards administering COVID‐19 vaccines to pregnant women. (30th June 2021) - Pramanick, Angsumita; Kanneganti, Abhiram; Wong, Jing Lin Jeslyn; Li, Sarah Weiling; Dimri, Pooja Sharma; Mahyuddin, Aniza Puteri; Kumar, Sailesh; Illanes, Sebastian Enrique; Chan, Jerry Kok Yen; Su, Lin Lin; Biswas, Arijit; Tambyah, Paul Anantharajah; et al.
Abstract: There are over 50 SARS‐CoV‐2 candidate vaccines undergoing Phase II and III clinical trials. Several vaccines have been approved by regulatory authorities and rolled out for use in different countries. Due to concerns of potential teratogenicity or adverse effect on maternal physiology, pregnancy has been a specific exclusion criterion for most vaccine trials with only two trials not excluding pregnant women. Thus, other than limited animal studies, gradually emerging development and reproductive toxicity data, and observational data from vaccine registries, there is a paucity of reliable information to guide recommendations for the safe vaccination of pregnant women. Pregnancy is a risk factor for severe COVID‐19, especially in women with comorbidities, resulting in increased rates of preterm birth and maternal morbidity. We discuss the major SARS‐CoV‐2 vaccines, their mechanisms of action, efficacy, safety profile and possible benefits to the maternal‐fetal dyad to create a rational approach towards maternal vaccination while anticipating and mitigating vaccine‐related complications. Pregnant women with high exposure risks or co‐morbidities predisposing to severe COVID‐19 infection should be prioritised for vaccination. Those with risk factors for adverse effects should be counselled accordingly. It is essential to support patient autonomy by shared decision‐making involving a risk‐benefit discussion with the pregnant woman. Key points: What is already known about this topic? COVID‐19 infection in pregnancy leads to an increase in adverse maternal outcomes. Owing to paucity of data regarding SARS‐CoV‐2 vaccine use in pregnancy there is uncertainty regarding safety of use and subsequent pregnancy outcomes. What does this study add? Provides an overview of the available SARS‐CoV‐2 vaccines, their mechanisms of action and feasibility of use in pregnancy. Summarises recommendations regarding vaccination of pregnant or lactating women.